"Eu sei, I know": Equity and Immigrant Experience in a Portuguese‐English Dual Language Bilingual Education Program. Issue 3 (6th August 2020) - Oliveira, Gabrielle; Lima Becker, Mariana; Chang-Bacon, Chris K.
Abstract : Recent scholarship reveals how English can be disproportionately privileged in dual language bilingual education (DLBE) programming (Cervantes‐Soon et al., 2017; Valdés, 1997). Through a program designed to serve Brazilian (im)migrant populations, this study expands the scope of DLBE research. This study took place in the U.S. state of Massachusetts, which has just emerged from a 15‐year period of English‐only legislation. It explores language status in a context of Portuguese Brazilian (im)migrant experience that has been largely unexplored in the TESOL literature. The researchers argue that there are three main dynamics of equity and language practices that need examination. While dual language teachers highly valued instruction in Portuguese, not all community stakeholders viewed Portuguese as a valuable language, accentuating inequalities in the experiences of children in the classroom. Brazilian immigrant children actively positioned themselves as experts during Portuguese instruction, however, often, they did not enjoy the attention and support that their English‐dominant peers experienced. Finally, Brazilian immigrant students' participation in the Portuguese‐led portions of the day was not conducive to further development of their advanced Portuguese knowledge. Through the combination of these dynamics, Brazilian immigrant children elevated the status of the language in their formal instructional environment, but were not themselves afforded a similarly high status.